POSITIVE ASPECTS AND / OR NEGATIVE EXPERIENCED BY ELDERLY: THE STRATEGY TO FOCUS ON THE FAMILY HEALTH (Fiep Bulletin - online, 2011)
The demographic time by passing the Brazilian population is characterized by low fertility rates, increased longevity and rapid urbanization. It is up to the professional attention to changes in the ESF population profile in their area, with the gradual increase of the elderly result of falling fertility and reduced mortality in all age groups. This is an exploratory-descriptive study with qualitative and quantitative approach. The study was carried out on-screen located on the paraibano Sousa. The main results indicate that participants were 36 elderly, characterized by a majority with 83% female, average age 69 years. In marital status, married seniors were predominant with 44%, observed that 64% second experience old age means a bad period. For rights, 81% of them mentioned that they are respected. Note that for 67% of respondents see as a positive point in FHS the care they receive. Already on the negative side, 43% reported no, 25% described the lack of medication. We conclude that there is a need to implement actions directed at the elderly enrolled in the ESF, whereas the increase of populations, the specific needs and multidimensional that seniors have, and especially the proposals of the PSF to be focused on promoting health, disease prevention, appropriate treatment and ensuring referrals and cross-reference to the more complex cases.
Keywords: Elderly; Family Health; Aging